2023
DOI: 10.1021/acsestengg.3c00192
|View full text |Cite
|
Sign up to set email alerts
|

Hexane Treatment to Facilely Tailor Polyamide Nanofiltration Membrane Performance: The Critical Role of Treatment Duration

Abstract: Facile methods for simultaneously tailoring various properties of nanofiltration (NF) membranes are of great significance for fit-for-purpose membrane design and thus achieving more efficient NF applications. This study revealed that, when preparing polyamide (PA) thin-film composite (TFC) NF membranes, a simple hexane treatment right after the interfacial polymerization reaction could substantially alter membrane properties and enhance separation performance for drinking water treatment, with the degree parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It is revealed that the pressure-normalized flux was greatly enhanced while retaining high salt rejection at about >95% ( Figure 15 ) compared to TFNC without an n-hexane rinse. The n-hexane rinse is beneficial to residual TMC monomers, creating a thinner PA-selective layer [ 67 ]. Based on XPS analysis ( Figure S5 ), after the n-hexane rinse, the O/N ratio dropped while the amide/carboxyl ratio increased ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is revealed that the pressure-normalized flux was greatly enhanced while retaining high salt rejection at about >95% ( Figure 15 ) compared to TFNC without an n-hexane rinse. The n-hexane rinse is beneficial to residual TMC monomers, creating a thinner PA-selective layer [ 67 ]. Based on XPS analysis ( Figure S5 ), after the n-hexane rinse, the O/N ratio dropped while the amide/carboxyl ratio increased ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…compared to TFNC without an n-hexane rinse. The n-hexane rinse is beneficial to residual TMC monomers, creating a thinner PA-selective layer [67]. Based on XPS analysis (Figure S5), after the n-hexane rinse, the O/N ratio dropped while the amide/carboxyl ratio increased (Table S3).…”
Section: The Effect Of Combined Heat-pressing and Hydrolysis On Thin-...mentioning
confidence: 99%
“…Nanofiltration (NF) has great promise for water treatment applications but is still challenged by the emergence of a variety of organic micropollutants (OMPs) in water. Conventional thin-film composite (TFC) nanofiltration membranes with a common molecular weight cutoff (MWCO) of 200–300 Da have high rejections of natural organic matters and divalent ions but are not effective enough at removing small-molecule OMPs with different physicochemical properties. , The intrinsic broad free volume distribution of polyamide (PA) selective layers also leads to a trade-off effect between permeability and selectivity of membranes. , To address this issue, extensive research has been conducted to optimize the structure and enhance the performance of TFC PA membranes by various approaches such as exploring novel reactive monomers, regulating the interfacial polymerization (IP) conditions, and introducing functional nanomaterials. Among them, the construction of an interlayer structure between the polyamide film and the porous substrate has shown advantages in tailoring membrane properties and performance for targeted water treatment applications. , …”
Section: Introductionmentioning
confidence: 99%